Paying a Debt to Society: Expunging Criminal Records as a Pathway to Increased Employment. Issue 1 (May 2022) - Crampton, Hakim Nathaniel
The American criminal justice system was built upon the premise of holding its citizens accountable for violations of law and upon being adjudicated and after having paid their prescribed punishment by a Court of Law, such citizens would be recognized as having "paid their debt" to society. However historical precedent has shown that very little of that premise has been practised. Instead citizens deemed felons of the law are perpetually punished by a series of lifetime collateral consequences, translating into an almost bar on access to employment and housing and other public rights. Expungement, or setting aside those convictions for people who've "paid their debt to society" is a clear pathway to increased access to employment for persons with a criminal record.